Liquid crystal electrolyte film, actuator, piezoelectric element and stress sensor
A novel liquid crystal electrolyte membrane composed of a zwitterionic compound, ionic liquid, and polymer addresses mixing issues in ion-conducting polymers, enabling actuators to operate at lower voltages with improved precision and mechanical functions.
Patent Information
- Application Number
- JP2021079821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-10
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-05-10
AI Technical Summary
Conventional ion-conducting polymers and liquid crystal electrolytes face challenges in uniform mixing at the molecular level, leading to difficulties in forming necessary ion conduction paths, and require high voltages for bending deformation, limiting the precision and efficiency of actuators.
A novel liquid crystal electrolyte membrane comprising a zwitterionic compound, ionic liquid, and polymer is developed, allowing for uniform mixing and formation of ion conduction paths, enabling actuators to bend at lower voltages and exhibit controlled mechanical functions.
The novel liquid crystal electrolyte membrane facilitates precise actuator movements at lower voltages, enhancing the mechanical properties and ion conductivity, and allows for the creation of self-supporting films with stretchability and self-healing capabilities.
Smart Images

Figure 0007607920000013 
Figure 0007607920000014 
Figure 0007607920000015
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystal electrolyte film containing a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer, and to an actuator, a piezoelectric element, and a stress sensor using the same. [Background technology]
[0002] There is an increasing demand for mechatronics devices that convert electrical energy into mechanical energy, such as industrial robot arms, humanoid robots, haptic devices for remote medical assistance and toys, and active medical catheters. To realize these devices, control methods using electromagnetic motors are being used. However, with control methods using electromagnetic motors, it is difficult to achieve delicate and smooth movements similar to those of biological muscles through electrical control, as is the case with artificial muscles, and they are relatively heavy and consume a lot of power. As a result, low-voltage driven soft actuators, which are lightweight and energy-efficient and operate smoothly and precisely over a wide range, have attracted attention as an alternative to such electromagnetic motors (Non-Patent Document 1).
[0003] Examples of such soft actuators include those that use ionically conductive polymers, those that use electronically conductive polymers, and those that use dielectric polymers, and new actuators that exhibit bending and stretching movements through electrical control, etc. have been proposed.
[0004] Among these, actuators using ion-conductive polymers have the excellent feature of exhibiting high-speed displacement at a relatively low voltage, as compared with actuators using other polymers. For example, Non-Patent Document 1 describes an actuator that uses an ion-conducting block copolymer to form an ion-conducting channel structure on the scale of several tens of nanometers, and that has both high ion conductivity and mechanical strength. Other known examples of ion-conductive polymers include perfluorosulfonic acid polymers (Nafion), vinyl polymer / ionic liquid gels (ion gels), and ion complexes of polyethylene glycol / lithium salt. Such actuators using ion-conducting polymers consist of a film made of an ion-conducting polymer with electrodes formed on both sides of the film. When a voltage is applied to the electrodes, ions in the ion-conducting polymer move, causing the film to bend and deform. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] O. Kim et al., Chem. Commun., 2018, 54, 4895-4904. Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the inventors' study, when a conventional ion-conducting polymer or a known liquid crystal electrolyte is used to compound an ion-conducting organic material, it has been found that there is a problem that the ions and the polymer and / or liquid crystal molecules are difficult to mix uniformly at the molecular level, and even if they are mixed, it is difficult to form the necessary ion conduction paths. In addition, actuators using conventional ion-conducting polymers have a problem that a voltage of about 4 V is required to cause bending deformation, and the inventors recognized that it is important to develop a material that shows bending displacement at a lower voltage.
[0007] The present invention has been made to solve the above problems, and aims to provide a novel liquid crystal electrolyte membrane, as well as an actuator, a piezoelectric element, and a stress sensor using the same, taking into consideration the ease of adjusting the liquid crystal structure, ion conductivity, heat resistance, elasticity, and other mechanical properties of the material used. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and have unexpectedly found that the above problems can be solved by using a novel liquid crystal electrolyte membrane, which has not existed in the past, comprising a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer, and have thus completed the present invention. That is, the gist of the present invention is as follows. [1] A liquid crystal electrolyte membrane comprising a liquid crystal electrolyte including a zwitterionic compound and an ionic liquid, and a polymer. [2] The liquid crystal electrolyte membrane according to [1], wherein the zwitterionic compound has an imidazolium sulfobetaine type structure. [3] The liquid crystal electrolyte membrane according to [1] or [2], wherein the zwitterionic compound is represented by formula (I): [ka] [4] The liquid crystal electrolyte membrane according to any one of [1] to [3], wherein the ionic liquid has a cation structure of any one of imidazolium, ammonium, pyridinium, sulfonium, piperidinium, pyrrolidinium, phosphonium, and morpholinium type. [5] The liquid crystal electrolyte membrane according to any one of [1] to [4], wherein the ionic liquid has a cation and an anion represented by formula (II): [ka] [6] The liquid crystal electrolyte membrane according to any one of [1] to [5], wherein the polymer in the liquid crystal electrolyte membrane includes polyvinyl alcohol, poly(vinylidene fluoride), or a perfluorosulfonic acid polymer. [7] The liquid crystal electrolyte membrane according to any one of [1] to [6], wherein the polymer in the liquid crystal electrolyte membrane is represented by formula (III): [ka] [8] An actuator comprising the liquid crystal electrolyte membrane according to any one of [1] to [7] and electrodes formed on both sides of the liquid crystal electrolyte membrane, wherein the liquid crystal electrolyte membrane is bent and deformed by applying a voltage between the electrodes. [9] The actuator according to [8], wherein the liquid crystal electrolyte film has a thickness of 10 μm to 1 mm.
[10] A piezoelectric element or stress sensor having a structure including the liquid crystal electrolyte membrane according to any one of [1] to [7] and electrodes formed on both sides of the liquid crystal electrolyte membrane, the structure generating electricity by deforming the structure. Effect of the Invention
[0009] According to the present invention, there is provided a novel liquid crystal electrolyte membrane comprising a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer. According to one aspect of the present invention, there is provided a novel composite liquid crystal electrolyte membrane comprising three components: liquid crystal molecules having a zwitterionic structure, an ionic liquid, and a polymer. According to the present invention, a novel actuator, piezoelectric element, and / or stress sensor is provided by using a novel liquid crystal electrolyte film including a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer.
[0010] According to one aspect of the present invention, by utilizing a zwitterionic liquid crystal electrolyte, it becomes possible to combine a variety of polar ionic liquids, acidic / basic organic molecules, and inorganic salts, thereby enabling the formation of ion conduction paths with one-dimensional to three-dimensional ordered structures and the adjustment of ion conductivity. Furthermore, by mixing various polymer materials as a third component into the liquid crystal electrolyte, it becomes possible to prepare free-standing membranes with controllable mechanical functions (e.g., elasticity and self-repairing functions), enabling more delicate control of actuator functions than with conventional materials. According to one aspect of the present invention, there is provided a novel electrically driven actuator that utilizes a liquid crystal electrolyte in which liquid crystal molecules and an ionic liquid are compatible at the molecular level and form an ion conduction path.
[0011] According to one aspect of the present invention, an actuator is provided that is constructed by using a novel composite liquid crystal electrolyte membrane containing three components, i.e., liquid crystal molecules having a zwitterionic structure, an ionic liquid, and a polymer, and sandwiching this between film-like electrodes, and that exhibits a desired bending displacement at a relatively low voltage, for example, a voltage lower than about 4 V. [Brief description of the drawings]
[0012] [Figure 1] This shows a polarizing microscope image at room temperature of a liquid crystal electrolyte obtained by mixing compound 1 and compound 2 (X=CF3SO3) in a molar ratio of 1:1. [Diagram 2] 1 shows an X-ray diffraction pattern at 70° C. of a liquid crystal electrolyte obtained by mixing compound 1 and compound 2 (X=CF3SO3) in a molar ratio of 1:1. [Diagram 3] (a) Left: A photograph of the film obtained by mixing compound 1 and compound 3 in a molar ratio of 1:3×10-3, coating the aqueous solution obtained on a polyimide film, and then drying (crystals of compound 1 precipitate, and the film does not become a free-standing film). (a) Right: A photograph of the film obtained by mixing compound 1, compound 2 (X=CF3SO3), and compound 3 in a molar ratio of 1:1:3×10-3, coating the aqueous solution obtained on a polyimide film, and then drying (free-standing film). (b): A photograph of the free-standing film on the right side of (a) above being lifted with tweezers. [Figure 4] 1 shows a polarizing microscope image at room temperature of a liquid crystal electrolyte film obtained by mixing Compound 1, Compound 2 (X=CF3SO3) and Compound 3 in a molar ratio of 1:1:3×10−3. [Diagram 5] 1 shows an X-ray diffraction pattern at 70° C. of a liquid crystal electrolyte film obtained by mixing Compound 1, Compound 2 (X=CF3SO3) and Compound 3 at a molar ratio of 1:1:3×10−3. [Figure 6] The structure and driving principle of the actuator element of the present invention, which is made of a liquid crystal electrolyte film and a conductive polymer (PEDOT-PSS), are shown. (a) No displacement when no voltage is applied, (b) Displacement occurs with voltage application. [Figure 7] Graph showing voltage (AC 0.1 Hz, 1 V) versus time and displacement at a position 5 mm from the end of a rectangular actuator of the present invention (measured at room temperature), (b) a photograph of the actuator when 0 V is applied, and (c) a photograph of the actuator when +1 V is applied. [Figure 8] (a) Graph showing voltage (1 Hz AC, 1 V) versus time and the displacement at a position 5 mm from the end of a rectangular actuator of the present invention (measured at room temperature), (b) a photograph of the actuator when 0 V is applied, and (c) a photograph of the actuator when +1 V is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiment is merely an example for explaining the present invention, and the present invention is not limited to the following embodiment.
[0014] <Liquid crystal electrolyte membrane> The liquid crystal electrolyte membrane of the present invention contains a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer. That is, the liquid crystal electrolyte membrane of the present invention is characterized by containing three components, i.e., a zwitterionic compound, an ionic liquid, and a polymer. Since the liquid crystal electrolyte membrane of the present invention contains a polymer (polymer) and has a film-like shape, it can also be called a liquid crystal electrolyte film, a liquid crystal polymer electrolyte membrane, a liquid crystal polymer electrolyte, a liquid crystal polymer electrolyte film, or a liquid crystal polymer electrolyte film.
[0015] In one embodiment of the present invention, a zwitterionic compound and an ionic liquid are mixed and self-assembled to provide an ionic conductor in which a continuous nanometer-scale ion conduction path is formed over a relatively long distance. As shown in the examples described later, a zwitterionic compound and an ionic liquid are self-assembled to form an ion conduction path arranged in a two-dimensional layer or one-dimensional column shape.
[0016] In one embodiment of the present invention, a liquid crystal electrolyte film having self-supporting properties can be provided by mixing a liquid crystal electrolyte including a zwitterionic compound and an ionic liquid with, for example, a specific polymer.
[0017] In one embodiment of the liquid crystal electrolyte membrane of the present invention, a liquid crystal electrolyte membrane having a desired shape, for example, a film-like shape having a desired thickness, can be provided by molding.
[0018] <Zwitterionic compounds> As the zwitterionic compound, zwitterionic liquid crystals or zwitterionic molecules can be used, for example, rod-shaped molecules in which imidazolium sulfobetaine-type structures are linked by covalent bonds can be used. As the zwitterionic compound, a compound having an imidazolium sulfobetaine type structure and also represented by the following formula (I) can be used. [ka] The zwitterionic compound may be a compound having a cationic onium structure such as quaternary ammonium or an anionic structure such as carboxylate, and may be a non-polymerizable compound or a polymerizable compound. The zwitterion compound is a molecule having a site in which a cation and an anion are covalently bonded within the molecule, and is preferably a thermotropic liquid crystal that exhibits liquid crystallinity upon application of heat. However, the zwitterion compound may not exhibit liquid crystallinity by itself, and may be a molecule that exhibits liquid crystallinity upon addition of an ionic liquid, an inorganic salt, an acid or a basic compound, water, or a polar solvent such as propylene carbonate. Since zwitterionic compounds have a site where a cation and an anion are linked, they do not usually exhibit high ionic conductivity. However, when they are placed in the presence of an ionic compound such as an ionic liquid or a polar solvent such as water, the ionic compound undergoes ionic dissociation at the zwitterionic site of the zwitterionic compound, forming an ion-conducting channel structure, which can result in high ionic conductivity.
[0019] <Ionic liquid> The ionic liquid is preferably a highly ion-conductive substance that has a wide potential window, is heat resistant, and is in a liquid state at room temperature. As the ionic liquid, an ionic liquid having any one of an imidazolium, ammonium, pyridinium, sulfonium, piperidinium, pyrrolidinium, phosphonium, or morpholinium type cation structure can be used. As the ionic liquid, a compound represented by the following formula (II) can be used. [ka] In addition, as the ionic liquid, a glyme-based lithium solvated ionic liquid or a deep eutectic solvent (a room temperature liquid that exhibits properties similar to an ionic liquid and is produced by mixing a hydrogen bond donor compound and a hydrogen bond acceptor compound in a certain ratio) may be used.
[0020] <Polymers contained in the liquid crystal electrolyte membrane> The polymer contained in the liquid crystal electrolyte membrane is preferably a polymer material capable of forming a self-supporting film, and from the viewpoint of ease of deformation, is more preferably a polymer having a glass transition temperature lower than room temperature. The polymer contained in the liquid crystal electrolyte membrane may be an ion-conductive polymer, and examples of the polymer that can be used include polyvinyl alcohol, poly(vinylidene fluoride), perfluorosulfonic acid polymer (Nafion), vinyl polymer / ionic liquid gel (ion gel), and polyethylene glycol / lithium salt ion complex. Furthermore, the polymer contained in the liquid crystal electrolyte film may be a poly(vinylidene fluoride)-poly(hexafluoropropylene) copolymer, polyethylene glycol, polyvinylpyrrolidone, polyethersulfone, butyl rubber, or the like. As the polymer contained in the liquid crystal electrolyte film, a compound represented by the following formula (III) can be used. [ka]
[0021] <Other features of the liquid crystal electrolyte membrane> In one embodiment of the present invention, the amount of ionic liquid in the liquid crystal electrolyte consisting of a zwitterionic compound and an ionic liquid before the polymer is incorporated to form a liquid crystal electrolyte membrane is preferably 10 mol % or more and 80 mol % or less. By keeping it within this range, there is an advantage that the liquid crystal electrolyte membrane can form a liquid crystal phase over a relatively wide temperature range. In addition, in one embodiment of the present invention, when a polymer is incorporated to form a liquid crystal electrolyte membrane, the amount of the polymer is preferably 20 mass % or more. This has the advantage that a free-standing film that imparts self-supporting properties to the liquid crystal electrolyte membrane can be obtained. In one embodiment of the present invention, the thickness of the liquid crystal electrolyte membrane after containing the polymer is preferably 10 μm or more and 1 mm or less. By keeping the thickness within this range, the film shape of the liquid crystal electrolyte membrane can be stabilized, and as described later, the function of an actuator, a piezoelectric element, or a stress sensor using the liquid crystal electrolyte membrane can be favorably exhibited.
[0022] <Actuator> The actuator of the present invention is a so-called soft actuator that has electrodes formed on both sides of the liquid crystal electrolyte membrane and can bend and deform the liquid crystal electrolyte membrane by applying a relatively low voltage, for example, a voltage of 1 V, between the electrodes. As an example, the actuator of the present invention may be an actuator in which electrode materials are bonded to both sides of a liquid crystal electrolyte membrane formed into a film shape composed of a zwitterionic liquid crystal, an ionic liquid, and a polymer.
[0023] In one embodiment of the present invention, the above-mentioned liquid crystal electrolyte membrane is sandwiched between two sheets of electronically conductive polymer films as electrodes, and a voltage is applied to these electrode films, whereby ions move from the liquid crystal electrolyte membrane to the surface of the electronically conductive polymer to form an electric double layer, and deformation of the liquid crystal electrolyte membrane is induced due to the difference in transport numbers and volumes between anions and cations. In addition, in one embodiment of the present invention, the migration of ions from the liquid crystal electrolyte film to the electronically conductive polymer film (layer) changes the redox state of the electronically conductive polymer film, causing ion doping and dedoping, which in turn causes the electrode material (electronically conductive polymer film) to swell and shrink, inducing deformation of the actuator.
[0024] The actuator of the present invention can control the functions required for the actuator by changing the chemical structures and / or mixture compositions of the zwitterionic compound, ionic liquid, and polymer (polymer), which are the components of the liquid crystal electrolyte membrane. The thickness of the liquid crystal electrolyte membrane provided in the actuator of the present invention is preferably 10 μm or more and 1 mm or less. By keeping it within this range, the film shape of the liquid crystal electrolyte membrane can be stabilized and the function of the actuator can be suitably expressed.
[0025] <Electrode> The electrodes sandwiching the liquid crystal electrolyte membrane of the present invention may be made of metal nanoparticles, nanowires, metal foil, carbon materials (activated carbon, graphene, carbon nanotubes, etc.), or conductive polymers (polypyrrole, PEDOT-PSS, etc.). In one embodiment of the present invention, a free-standing film of an electronically conductive polymer, so-called PEDOT-PSS (poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid)), doped with ethylene glycol can be used as an electrode, and this electrode film can be pressed against a liquid crystal electrolyte membrane to produce an actuator element.
[0026] <Application as a piezoelectric element or stress sensor> The actuator of the present invention is an actuator element that generates a displacement or vibration in response to application of a voltage to the liquid crystal electrolyte membrane of the present invention, and therefore can be used as a piezoelectric element by utilizing the piezoelectric effect of the liquid crystal electrolyte membrane, and can also be used as a stress sensor that generates a voltage in response to stress deformation of the liquid crystal electrolyte membrane. A structure in which electrodes are formed on both sides of the liquid crystal electrolyte membrane can be formed, and a piezoelectric element or stress sensor that generates electricity by deforming the structure can be provided. EXAMPLES
[0027] The preparation and characteristics of the lithium-air battery of the present invention will be described in more detail below based on examples. Note that these descriptions are merely illustrative of the embodiments of the present invention, and the present invention is not limited to these examples.
[0028] [Example 1] Examination and evaluation of the fabrication process of liquid crystal electrolyte membrane The zwitterionic compound represented by formula (I) (which refers to zwitterionic molecule 1 of formula 1 below, and may hereinafter be referred to as "compound 1") was synthesized according to the following reaction scheme. [ka]
[0029] Next, compound 1 and the ionic liquid represented by formula (II) (which refers to an imidazolium-type ionic liquid represented by formula 2(X) below, and may hereinafter be referred to as "compound 2," "compound 2(X)," or "ionic liquid 2(X)") were mixed at 50 mol % or less to obtain a desired composition, thereby preparing a liquid crystal electrolyte before incorporating a polymer. [ka] These binary mixtures were obtained by mixing weighed amounts of each molecule with heat, but also by evaporating the solvent in methanol. It was found that the mixtures of these two components formed liquid crystal layers over a wider temperature range, including room temperature, than the compound 1 molecules alone. When the anion (X) of ionic liquid 2(X) was changed within the range of options described in formula (II) above, it was found that the liquid crystal structure formed changed depending on the selected anion (X). Specifically, when the composition of ionic liquid 2(X) was 50 mol%, a columnar liquid crystal phase that formed a one-dimensional ion conduction path appeared when X=BF4 or CF3SO3, while a smectic liquid crystal phase that formed a two-dimensional ion conduction path appeared when X=PF6 or (CF3SO2)2N.
[0030] Next, a polymer was mixed into the two-component liquid crystal electrolyte to obtain a self-supporting liquid crystal electrolyte film. Specifically, the following conditions were used. Under certain conditions, a two-component liquid crystal electrolyte was mixed with more than 20% by weight of vinyl polymer polyvinyl alcohol (degree of polymerization 2000, saponification rate 80 mol%) to obtain a self-supporting liquid crystal electrolyte membrane with a columnar structure and exhibiting elasticity. Under different conditions, a 10 wt % aqueous solution of polyvinyl alcohol represented by the above formula (III) (referring to the polymer of the following formula 3, hereinafter sometimes referred to as "compound 3") was added to a two-component liquid crystal electrolyte in a glass bottle, and the mixture was stirred and mixed using a magnetic stirrer to prepare a homogeneous solution. This solution was then transferred into a Teflon petri dish and dried by heating to obtain a film-like, self-supporting liquid crystal electrolyte membrane. [ka] Furthermore, under different conditions, a free-standing liquid crystal electrolyte film exhibiting repeated bending properties was obtained by adding and mixing more than 20 wt% poly(vinylidene fluoride) into a two-component liquid crystal electrolyte.
[0031] [Example 2] liquid crystal electrolyte membrane < a. Synthesis of zwitterionic compound (compound 1) > In a round-bottom flask under an inert argon atmosphere, 4-(trans-4-pentylcyclohexyl)phenol (4.2 g), 1,6-dibromohexane (20.7 g), and potassium carbonate (7.0 g) were suspended in dehydrated N,N-dimethylformamide (100 mL) and stirred at 80° C. for 14 hours. The resulting reaction solution was cooled to room temperature, then separated and extracted with a saturated aqueous ammonium chloride solution and hexane. The organic layer was separated and dehydrated by adding anhydrous magnesium sulfate. The mixture was then filtered, the solvent was distilled off under reduced pressure, and the pressure was reduced to 120° C. to remove excess 1,6-dibromohexane. The resulting solid residue was then dissolved in hexane and purified by silica gel chromatography (developing solvent: hexane) to obtain compound 4 (3.2 g, 46% yield) as a white solid described in the above reaction scheme.
[0032] Next, in a side-arm round-bottom flask under an inert argon atmosphere, a small amount of dehydrated tetrahydrofuran was added to 60% sodium hydride (0.62 g) while cooling the flask in a water bath, and then a solution of imidazole (1.0 g) in dehydrated tetrahydrofuran (20 mL) was added dropwise through a septum cap, and then reacted at room temperature for 10 minutes. Next, a solution of compound 4 (3.2 g) in tetrahydrofuran (20 mL) was added dropwise to the resulting reaction solution, and then reacted at 80° C. for 12 hours. After cooling the resulting reaction solution to room temperature, it was separated and extracted with ethyl acetate and water, and anhydrous magnesium sulfate was added to the extract to dry it. Then, it was filtered, and the filtrate was dried under reduced pressure. Next, the obtained solid residue was dissolved in hexane and purified by silica gel chromatography (developing solvent: ethyl acetate) to obtain compound 5 (2.1 g, yield 68%) as a white solid described in the above reaction scheme.
[0033] Next, in a round-bottom flask under an inert argon atmosphere, 1,3-propane sultone (0.99 g) was added dropwise to a solution (10 mL) of compound 5 (1.6 g) in dehydrated dichloromethane, and the mixture was stirred at room temperature for 2 days. The resulting reaction solution was then concentrated, purified by silica gel chromatography (developing solvent: a mixture of chloroform and methanol in a volume ratio of 85:15), and further recrystallized using ethyl acetate to obtain compound 1 (1.5 g, 74% yield) as a white solid, as described in the above reaction scheme. The obtained compound 1 (element composition C 29 H 46 The measured and theoretical values of elemental analysis of N2O4S were as follows: Measurements: C, 67.43; H, 8.83; N, 5.33; S, 6.46 Theoretical values: C, 67.14; H, 8.94; N, 5.40; S, 6.18.
[0034] < b. Zwitterionic compound (compound 1) and imidazolium-type ionic liquid (compound 2 (X=CF 3 SO 3 Preparation and structural analysis of liquid crystal electrolytes composed of two components <Preparation of Liquid Crystal Electrolyte> A liquid crystal electrolyte was prepared by mixing the above-mentioned compound 1, which is a zwitterionic compound, with compound 2, which is an imidazolium-type ionic liquid (ionic liquid 2 (X=CF3SO3)), in a molar ratio of 1:1. More specifically, the molecules of each compound were weighed out and mixed under heating, or were dissolved in methanol, and the solvent was then evaporated to obtain a liquid crystal electrolyte in which an ion pair was formed at the zwitterionic site due to ionic dissociation of the ionic liquid at the zwitterionic site of the zwitterionic compound.
[0035] <Structural analysis> The liquid crystal electrolyte obtained by mixing compound 1 and compound 2 (X=CF3SO3) in a molar ratio of 1:1 was observed using a polarizing microscope at room temperature and was also subjected to X-ray diffraction measurement at 70° C. The obtained polarizing microscope image and X-ray diffraction pattern are shown in Figures 1 and 2, respectively. As can be seen from Figure 1, in the liquid crystal electrolyte obtained by mixing compound 1 and compound 2 (X = CF3SO3) in a molar ratio of 1:1, a birefringence image suggesting the formation of a columnar liquid crystal structure was observed. As can be seen from Figure 2, the X-ray diffraction pattern of this liquid crystal electrolyte contained a peak with a d value of 45 Å, which is thought to be due to diffraction from the 100 plane of the hexagonal columnar structure, a peak with a d value of 23 Å, which is thought to be due to diffraction from the 200 plane, and a halo peak with a d value of 4.6 Å, which is due to the motion of the alkyl chains of compound 1.
[0036] < c. Zwitterionic compound (Compound 1), imidazolium ionic liquid (Compound 2 (X=CF 3 SO 3 Preparation and structural analysis of liquid crystal electrolyte membranes composed of three components: 1) and polyvinyl alcohol (compound 3) > <Preparation of Liquid Crystal Electrolyte Film> In a glass bottle, a liquid crystal electrolyte composed of the above compound 1 (162 mg), which is a zwitterionic compound, and the above compound 2 (ionic liquid 2 (X=CF3SO3)) (90 mg), which is an imidazolium-type ionic liquid, was added with a 10% by weight aqueous solution of the above compound 3 (polymerization degree 2000, saponification rate 80 mol%) (75 mg), which is a polymer of polyvinyl alcohol, and stirred and mixed using a magnetic stirrer to prepare a homogeneous solution. At this time, the molar ratio of the compounds 1, 2, and 3 was 1:1:3×10 -3 It was. The obtained solution was applied to a glass substrate with polyimide tape attached and then heated and dried under vacuum to obtain a self-supporting liquid crystal electrolyte film (the weight ratio of liquid crystal electrolyte to polymer was 77% by weight:23% by weight).
[0037] A photograph of the obtained liquid crystal electrolyte membrane and a photograph of the obtained liquid crystal electrolyte membrane lifted up with tweezers are shown on the right side of Figure 3(a) and Figure 3(b), respectively. These photographs show that the obtained liquid crystal electrolyte membrane certainly exhibits self-supporting properties.
[0038] <Structural analysis> In this way, compound 1, compound 2 (X=CF3SO3) and compound 3 were mixed in a molar ratio of 1:1:3×10 -3The liquid crystal electrolyte film obtained by mixing the above was observed with a polarizing microscope at room temperature and was also subjected to X-ray diffraction measurement at 70° C. The obtained polarizing microscope image and X-ray diffraction pattern are shown in FIG. 4 and FIG. 5, respectively. As can be seen from FIG. 4, compound 1, compound 2 (X=CF3SO3), and compound 3 were mixed in a molar ratio of 1:1:3×10 -3 In the liquid crystal electrolyte film obtained by mixing the above, a birefringence pattern due to the liquid crystal formation was observed. Furthermore, as can be seen in Figure 5, the X-ray diffraction pattern of this liquid crystal electrolyte membrane contained a peak with a d value of 47 Å, which is thought to be due to diffraction from the 100-plane of the hexagonal columnar structure, and a halo peak with a d value of 4.6 Å, which is due to the motion of the alkyl chains of compound 1.
[0039] In addition, in this ternary liquid crystal electrolyte film, the d value, which is thought to be derived from diffraction from the 100th plane of the hexagonal columnar structure, increased by 2 Å, from 45 Å to 47 Å, compared with the above-mentioned two-component liquid crystal electrolyte (liquid crystal electrolyte obtained by mixing compound 1 and compound 2 (X=CF3SO3) at a molar ratio of 1:1). This suggests that the columnar structure expanded due to the organization of polyvinyl alcohol inside the ion-conducting channel structure located at the center of the columnar structure formed by the liquid crystal electrolyte.
[0040] [Comparative Example 1] A composition consisting of a zwitterionic compound (compound 1) and polyvinyl alcohol (compound 3) and not containing ionic liquid The solution was applied to a glass substrate with a polyimide tape attached in the same manner as in Example 2c, except that the mixed solution was prepared without the ionic liquid compound 2 and by using dimethyl sulfoxide, which is a common solvent for compounds 1 and 3, instead of water. The reason for using dimethyl sulfoxide instead of water is that compound 1 alone is insoluble in water. A photograph of the product obtained by the above heat drying is shown on the left side of Figure 3(a). From this photograph, it can be seen that the product obtained as a result of the heat drying is not a film that shows self-supporting properties, unlike Example 2. This is thought to be because compound 1 precipitated as powdery crystals from compound 3, which is a polymer.
[0041] [Example 3] Actuator < a. Preparation of electrode film > In a glass bottle, 6.0% by volume of ethylene glycol was added to a 1.3% by weight aqueous solution of PEDOT-PSS (Sigma-Aldrich), an electronic conductive polymer, and stirred to create a homogeneous solution. This solution was then transferred to a Teflon petri dish, heated and dried at 60°C, and further heat-treated at 120°C to obtain a self-supporting PEDOT-PSS film.
[0042] < b. Fabrication of actuator elements > The liquid crystal electrolyte membrane obtained by the method of Example 2 (thickness: 35 μm, ionic conductivity at 25° C.: 3×10 -5 A rectangular actuator element (length 15 mm, width 5 mm, thickness 40 μm) was fabricated by sandwiching a 10-μm thick PEDOT-PSS film between two self-supporting electrode films (thickness 10 μm) and pressing them together using a press.
[0043] < c. Actuator evaluation method> Copper foil was placed on both sides of one end of the rectangular actuator element as a current collector, and the actuator was placed in a homemade actuator evaluation device. A square wave from a function generator was connected to a potentiogalvanostat, and a voltage was applied to the electrode terminals of the actuator. The voltage applied to the actuator and the current associated with ion movement were recorded in a data logger (manufactured by Hioki). The displacement of the actuator was measured with a laser displacement meter (manufactured by Keyence) and recorded in the data logger. These evaluations were performed at room temperature.
[0044] < d. Actuator characteristics > When a rectangular AC voltage of 1 V was applied to the rectangular actuator element (see Fig. 6(a)), it bent toward the positive electrode. This was because, as shown in Fig. 6(b) diagrammatically, large cations accumulated on the negative electrode side of the actuator (the lower side of the figure), causing it to swell.
[0045] Figures 7(a), (b), and (c) show the results when a square wave of AC voltage 1V was applied with a frequency of 0.1Hz. Figure 7(a) is a graph showing the voltage (AC 0.1Hz, 1V) versus time and the displacement at a position 5mm from the end of the rectangular actuator, while Figures 7(b) and 7(c) show photographs of the actuator when 0V and +1V were applied, respectively. As can be seen from these figures, when an AC voltage of only 1V was applied as a square wave with a frequency of 0.1Hz, a displacement of 2mm was confirmed at a position 5mm from the end of the rectangular actuator.
[0046] On the other hand, Figures 8(a), (b), and (c) show the results when a voltage was applied with a square wave frequency of 1 Hz. Figure 8(a) is a graph showing the voltage (1 Hz AC, 1 V) versus time and the displacement at a position 5 mm from the end of the rectangular actuator, while Figures 8(b) and 8(c) show photographs of the actuator when 0 V and +1 V were applied, respectively. As can be seen from these figures, when an AC voltage of just 1 V was applied as a square wave with a frequency of 1 Hz, it was confirmed that the displacement of the rectangular actuator at a position 5 mm from the end of the rectangular actuator was 1 mm, reduced compared to the case of 0.1 Hz. [Industrial Applicability]
[0047] According to the present invention, a novel liquid crystal electrolyte membrane containing a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer can be provided, and by using such a novel liquid crystal electrolyte membrane, a novel actuator, a piezoelectric element, and / or a stress sensor can be provided. Therefore, the present invention is expected to be suitably used in various fields that can utilize ion-conductive liquid crystal materials that have excellent electrochemical and mechanical properties, are lightweight and have excellent energy saving properties, and are expected to see a significant increase in demand in the future. [Explanation of symbols]
[0048] 1 Liquid crystal electrolyte membrane (comprising a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer) 2 Electrode (electronically conductive polymer) 3 Current collector (copper foil) 4 Anions that compose ionic liquids 5. Cations that compose ionic liquids
Claims
1. A liquid crystal electrolyte membrane comprising a liquid crystal electrolyte containing a zwitterionic compound and an ionic liquid, and a polymer, wherein the zwitterionic compound has an imidazolium sulfobetaine type structure.
2. The liquid crystal electrolyte membrane according to claim 1 , wherein the zwitterionic compound is represented by formula (I): 【Chemistry 1】
3. 3. The liquid crystal electrolyte membrane according to claim 1, wherein the ionic liquid has any one of an imidazolium, ammonium, pyridinium, sulfonium, piperidinium, pyrrolidinium, phosphonium, and morpholinium type cation structures.
4. The liquid crystal electrolyte membrane according to any one of claims 1 to 3, wherein the ionic liquid has a cation and an anion represented by formula (II): 【Chemistry 2】
5. The liquid crystal electrolyte membrane according to any one of claims 1 to 4, wherein the polymer in the liquid crystal electrolyte membrane comprises polyvinyl alcohol, poly(vinylidene fluoride), or a perfluorosulfonic acid polymer.
6. The liquid crystal electrolyte membrane according to any one of claims 1 to 5, wherein the polymer in the liquid crystal electrolyte membrane is represented by formula (III): 【Chemistry 3】
7. 7. An actuator comprising the liquid crystal electrolyte membrane according to claim 1 and electrodes formed on both sides of the liquid crystal electrolyte membrane, the liquid crystal electrolyte membrane being bent and deformed by applying a voltage between the electrodes.
8. 8. The actuator according to claim 7, wherein the liquid crystal electrolyte film has a thickness of 10 μm to 1 mm.
9. 7. A piezoelectric element or stress sensor comprising a structure having the liquid crystal electrolyte membrane according to claim 1 and electrodes formed on both sides of the liquid crystal electrolyte membrane, the structure generating electricity by deformation of the structure.
Citation Information
Patent Citations
Piezoelectric transduction composite material
JP2005203590A
Actuator
JP2013123366A
Electrolyte for actuator element and actuator element
JP2016119801A
Stiffness control of electroactive actuators
JP2019536404A